How systemic cognition enables epistemic engineering - Cowley, Stephen J.; Gahrn-Andersen, Rasmus (Frontiers in Artificial Intelligence, 2023)
Epistemic engineering arises as systems and their parts develop functionality that is construed as valid knowledge. By hypothesis, epistemic engineering is a basic evolutionary principle. It ensures that living systems not only identify differences that make differences (Bateson, 1979) but, at once, distributed control enables them to construct epistemic change. In tracking such outcomes in human life, we stress that humans act within poly-centered, distributed systems. Just as people can act as inert parts of a system, they also actively bring forth intents and vicariant effects. Human cognitive agents use systemic function to construct epistemic novelties. In illustration, we use Li & Zhang’s (2016) experimental study of a cyborg cockroach to consider how an evoneered system enables a human subject to perform as an adaptor with some ‘thought control’ over the animal. Within a wide system, brains enable techniques to arise ex novo as they attune to the dictates of a device. Human parts act as adaptors that simplify the task. In scaling up, we turn to a case of organizational cognition. We track how adaptor functions spread when drone-based data are brought to the maintenance department of a Danish utility company. While pivoting on how systems-operators combine experience with use of software, their expertise sets off epistemically engineered results across the company and beyond. Vicariant effects emerge under the poly-centered control of brains, persons, equipment and institutional wholes. As part of culture, epistemic engineering works by reducing entropy.